Severe hyperparathyroidism is associated with nutritional impairment in maintenance hemodialysis patients - Disthabanchong, Sinee; Vantanasiri, Kornpong; Khunapornphairote, Sirote; Chansomboon, Payupol; Buachum, Nuchcha; Saeseow, Sarunya (Frontiers in Nutrition, 2022)
Severe hyperparathyroidism predicts poor outcomes in patients with kidney failure. Mechanisms underlying the relationship between high parathyroid hormone (PTH) and decreased survival other than bone loss are largely unexplored. Recent evidence suggests the role of excess PTH in adipose tissue browning resulting in protein-energy wasting. The present retrospective observational study examined nutritional status among patients receiving maintenance hemodialysis with different degree of hyperparathyroidism. Seven hundred forty-five patients were categorized into 4 groups according to PTH levels: group 0, <200; group 1, 200-599; group 2, 600-1499; and group 3, ≥1500 pg/mL. Group 0 was excluded because of the relationship between low PTH with aging and malnutrition. Patients in groups 1 and 2 were matched to group 3 by propensity score yielding 410 patients in the final analysis. Nutritional parameters at baseline and the preceding 1 and 2 years were examined. At baseline, lower serum albumin, creatinine/body surface area (Cr/BSA), height in female and higher percentage of patients with serum albumin <38 g/L were observed in group 3 compared to groups 1 and 2. Higher PTH level was independently associated with serum albumin <38 g/L and Cr/BSA <380 μmol/L/m2. The longitudinal decline in serum albumin and Cr/BSA and the increase in the frequency of patients with serum albumin <38 g/L were observed among patients in group 3. Between group comparisons confirmed a significant decline in serum albumin and Cr/BSA in association with an increase in the proportion of patients with serum albumin <38 g/L and Cr/BSA <380 μmol/L/m2 in group 3 compared to groups 1 and 2. Weight loss was more significant and was of greater magnitude among patients in group 3 compared to groups 1 and 2. Normalized protein catabolic rate in 3 groups were comparable. There was no significant difference in any of the nutritional parameters between groups 1 and 2. In conclusion, patients receiving maintenance hemodialysis with severe hyperparathyroidism showed deterioration of nutritional status compared to patients with moderate hyperparathyroidism and patients with PTH level in the recommended range. These findings support the role of extreme PTH level in protein-energy wasting emphasizing the importance of early management of hyperparathyroidism.